Anthropocentric urban creativity: sketching, drawing and painting, as research tools - Neves, Pedro Soares (BBDS - Black Book: Drawing and Sketching, 2021)
This essay touches two very unstable realms. The first deals with the relation of “urban design” and anthropocentrism, and the second with sketching, drawing and painting, as research tools. This said, it is only with exploratory pretension that this essay is shared. It is not intended to prove any stable point of view. In fact it follows ongoing experimental development based on sketching, drawing and painting practises. This experimental endeavour it is related with several personal and altruistic purposes. The usage of sketching, drawing and painting as mediums for inflicting changes on society it is a long term personal endeavour (since teenager). To use this resources as tools for visual realm dessication are part of a relevant emotional path and flows in a natural and fulfilling way. The dessication is needed as resolution path for issues that found in my environment (Lisbon), biut can also be found in most of the urban environments.